Coming to know writing to learn in the intermediate grades - Atwell, Nancie (Heinemann, 1990)
"Coming to Know is a book for teachers who are ready to put writing to work across the curriculum. It is written by teachers of grades 3 through 6 who, dissatisfied with encyclopedia-based approaches to content-area writing, asked their students to write as scientists, historians, mathematicians, and literary critics do--to use writing-as-process to discover meaning. One of the subjects of this volume is report writing and ways to help children produce content-area writing that is as personal and meaningful as their stories of their own experiences. Students learn how to take notes in their own words, conduct interviews, record observations, design their first simple research project, select appropriate genres for their research, and apply the techniques of writing workshop in science, social studies, and reading classes. In addition, Coming to Know explores the uses of academic journals, or learning logs. Children speculate, brainstorm, role play, correspond, predict, and ask questions about math, reading, science, and social studies--and demonstrate the power of informal writing to generate thinking. Coming to Know is also about the connections between reading and writing, the effects of using writing to learn on curriculum and planning, and the role of children's literature in teaching science, social studies and math."--Publisher's description.